Trust based secure de-forestation and timber theft alert in wireless sensor networks - N. Renjith, P (International Journal of Engineering and Technology, 2018)
Deforestation is the permanent destruction of trees for timber and land. Deforestation and timber theft ends up with obliteration of entire forest in the earth. Deforestation has increased exponentially increase in this decade. It is well known that Deforestation is a prime reason for global warming, less tropical rainfalls and affects atmospheric oxygen level. In this paper, a novel query-based method has been intro-duced to alert deforestation to forest official. Trust analysis and data aggregation has been incorporated to improve security and fast trans-mission of information to the base station. Query based technique is used to evaluate the intrusion has been implemented. Simulation result proven that the ST-alert able to detect the trespasser and stop them from deforestation.Â